AUTHORIZED CAPITAL AS A RISK MANAGEMENT TOOL IN EMERGING ECONOMIES. THE CASE OF POLAND - Adamska, Agata; Staszkiewicz, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Abstract: This paper addresses the strength of the incentives from both supervisors and market players to use authorized capital application as a risk management tool. The study contrasts the motivational factors for the financial market in transition and market supervisor. It analyses the interaction between motivation and the application of authorized capital as a risk management tool. We challenge the hypothesis that there is a weak statistical relationship between goodwill rates and the existence of authorized capital instruments for quoted companies and a weak statistical relationship between bank allowance and authorized capital instruments. Through the application of logit procedures to companies quoted on the Warsaw Stock Exchange, we conclude findings based on 386 listed and domiciled entities in Poland, as quoted on the of 30 December 2011. We conclude a semi-effective market suffers from efficiency in adoption of authorized capital as a risk management tool. We indicate that market forces are overridden by supervisory requirements; thus, the promotion of effective risk management tools is positively associated with regulator and supervisory activities.